2019
DOI: 10.1093/jac/dkz444
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian clinical decision support-guided versus clinician-guided vancomycin dosing in attainment of targeted pharmacokinetic parameters in a paediatric population

Abstract: Objectives To compare a Bayesian clinical decision support (CDS) dose-optimizing software program with clinician judgement in individualizing vancomycin dosing regimens to achieve vancomycin pharmacokinetic (PK)/pharmacodynamic (PD) targets in a paediatric population. Methods A retrospective review combined with a model-based simulation of vancomycin dosing was performed on children aged 1 year to 18 years at the University o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…These samples overestimated vancomycin concentrations compared to correctly timed samples, resulting in an increased likelihood of prescribers incorrectly reducing, discontinuing or withholding doses 6 . Dose‐prediction software is an increasingly popular intervention that has the potential to improve vancomycin dosing 8–11 . State of the art dose‐prediction software uses Bayesian forecasting to integrate readily available patient data with validated population pharmacokinetic models to provide individualised dose recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…These samples overestimated vancomycin concentrations compared to correctly timed samples, resulting in an increased likelihood of prescribers incorrectly reducing, discontinuing or withholding doses 6 . Dose‐prediction software is an increasingly popular intervention that has the potential to improve vancomycin dosing 8–11 . State of the art dose‐prediction software uses Bayesian forecasting to integrate readily available patient data with validated population pharmacokinetic models to provide individualised dose recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…18 The study was also not Bayesian dosing tool to be better than clinician judgement in recommending vancomycin dosing regimens. 25 We consider this a conservative improvement, since mean AUC 24 and %TTR could have been further improved had we used higher loading doses. The loading dose used during this study was according to hospital guideline rather than DoseMeRx.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recently reported study of vancomycin dosing in children by Hughes et al produced very similar results to our study. The authors found that Bayesian tool guided dosing regimens were predicted to achieve vancomycin steady‐state troughs in the therapeutic range 10–15 mg/L on 70.8% of occasions compared to 37.5% in the clinician guided arm, showing the use of a Bayesian dosing tool to be better than clinician judgement in recommending vancomycin dosing regimens 25 …”
Section: Discussionmentioning
confidence: 99%
“…In the past few decades, many studies have supported the use of the PopPK model to optimize vancomycin dosage schedule. 4,5 Because the sampling method is more convenient for patients, the PopPK has become a practical tool. Vancomycin has a narrow therapeutic index and shows high inter-individual variability, making the dosage adjustment challenging.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%